DETERMINANTS OF EMPLOYEE RETENTION MILLENNIALS WORKFORCE AT PT ASURANSI JASARAHARJA PUTERA - Nuraeni Nuraeni; Siti Mariyam; Rifzaldi Nasri (Sosiohumaniora, 2022)
The abundance of knowledge possessed by the company can be utilized optimally to improve company performance to create the best products, services, business processes, and customer services. Less than optimal utilization of knowledge can hamper the company’s performance and not solve various problems. The problems faced by many companies in the past and now, between branch/representative offices and between divisions/other work units, are often the same. Personnel turnover is another reason why the company cannot utilize one’s knowledge. The purpose of this study is focused on determining the impact of Knowledge Management and Talent Management on Employee Retention in the case of the Millennials Workforce. Previous research found that Human Resources Development Manager dealing with the Generation of Millenials where are the generation that can adapt to the environment and is dominated by the use of Information Technology in carrying out the work. The population in this research is Employees of PT Jasarahraja Son. The questionnaire was used to collect data on as many as 60 respondents through simple random sampling. The data used in this research is a quantitative analysis using Structural Equation Modeling (SEM) Partial Least Square method (PLS) with the program Warp PLS 5.0. The Test results showed that the coefficient of determination which looks at the value Adjusted R-Square is 0.69, which means that employee retention can be explained by the variable of Knowledge Management and Talent Management by 69%. The remaining 31% is explained by other variables that are not observed in the study.